Bouba cutânea atípica e mista em frangos caipiras vacinados no Nordeste brasileiro. - Sousa, Rafanele Trajano (2019)
Avian bouba is a worldwide disease caused by an avipoxvirus of the poxviridae family. In recent years, studies and reports have denoted variations in the form of the disease, with the discovery of new variants and characteristics of infection, requiring monitoring of cases with reports of epidemiological interactions of avipoxviruses with their vectors and hosts. For this purpose, this work describes an outbreak of atypical of avian bouba in vaccinated broiler. The outbreak occurred in Alagoa Grande-PB, rearing 180 birds, which presented delayed growth and infestation by Dermanyssus gallinae. We identified 40% of the birds with nodules on the skin and 20% of them were associated with runny nose and conjunctivitis. At necropsy, nodular lesions were observed throughout the body of birds. Pseudomembranes and caseous masses were found in the upper respiratory tract and cranial cervical and thoracic air sacs. On microscopy, moderate orthokeratotic hyperkeratosis was observed in the epidermis and baloneous degeneration, with Bollinger bodies in the superficial dermis. In the lung there was a loss of architecture of the parabronchia with hyperplasia of the epithelium and formation of diphtheria membranes in the lumen. Necrosis and fibrosis in the spleen and liver. The verification of inflammatory changes associated with corpuscles of intracytoplasmic inclusions allowed the confirmation of avian bouba with atypical distribution of lesions, resulting from the interaction with Dermanyssus gallinae. In this case, the control and subsequent prevention measures were effective, but given the impactful characteristics of this case, it is necessary to carry out further research for data aggregation, and monitoring on the topic in regional poultry farming.